Load training on instabile surfaces - an important addition to traditional strength training programs - Kibele, A.; Behm, D. (Science and Skiing V. 5th International Congress on Science and Skiing, Dec. 14 - 19, 2010, St. Christoph am Arlberg, 2012)
INTRODUCTION: Various games sports, combat sport, and outdoor activities require a force development in open skills that are executed under instable environmental conditions (e.g. perturbing opponents, instable surfaces, adverse weather conditions). However, traditional strength training programs are commonly related to a force development exercises under stable conditions only. This paper introduces a load training on instable surfaces that is thought to complement traditional strength training programs. Training effects related to functional testing procedures were used to compare both strength training categories.